The Relationship of Experience, Satisfaction, and Trust of Y Generation Tourist Instagram Social Media Users to Tourism Destination Loyalty in Yogyakarta - Syamsu, Moch Nur; Sasongko, Gatot; Andadari, Roos Kities; Supramono, Supramono (Technium Social Sciences Journal, 2022)
The purpose of this study is to understand the factors of Y Generation Instagram users in choosing tourism destinations, so that they can be a reference for community groups to develop innovative products based on potential resources and human resource competencies to design sustainable and competitive authentic products. This research uses quantitative method. Purposive sampling is a technique for determining research samples with certain considerations aimed at making the data obtained more representative. The number of samples used as many as 385 people belonging to Y Generation, who have visited a tourism destination in the Special Region of Yogyakarta more than once and as users of social media Instagram. To test the hypothesis empirically using the AMOS 2.2 application. A decision-making model regarding tourism destination loyalty by exploring the influence of experience, satisfaction, trust and loyalty to tourism destinations. In addition, it also includes a moderating variable for the use of Instagram social media which is expected to strengthen the influence on tourist destination loyalty and take the object of Y Generation. Researchers found that the use of Instagram social media strengthens the experience, satisfaction, and trust of Y Generation towards loyalty to tourism destinations in the Special Region of Yogyakarta.